Sample size to estimate biomass and productivity of Canavalia ensiformis and Dolichos lablab - Teodoro, Paulo E. (2019)
Green manure brings numerous benefits that promote essentially the maintenance and conservation of agro-systems, and its implementation is fundamental to Brazilian Cerrado region. In this scenario, the present research aimed to determine the sample size for the estimation of biomass and productivity expected values of Canavalia ensiformis and Dolichos lablab. The experiment was installed in the experimental area of the State University of Mato Grosso do Sul - Unit University Aquidauana (UEMS/UUA), located in the Brazilian Cerrado. Forty five plants were randomly selected in the experimental area of each crop to determine fresh mass, dry mass and yield. Measures of central tendency, variability, asymmetry and kurtosis were calculated and normality of the variables under study was checked by the Lilliefors test. In C. ensiformis and D. lablab, 259 and 362 plants, respectively, are sufficient for the estimation of evaluated variables, with confidence interval of 95% an estimation error equal to 5% of the observed average. C. ensiformis showed significant high mean values for the fresh mass production, dry mass and yield grain in comparison with the Dolichos lablab, being recommended for cultivation in Brazilian Cerrado.